2007
DOI: 10.1038/sj.npp.1301635
|View full text |Cite
|
Sign up to set email alerts
|

α1-Adrenergic Receptor-Induced Heterosynaptic Long-Term Depression in the Bed Nucleus of the Stria Terminalis Is Disrupted in Mouse Models of Affective Disorders

Abstract: The glutamatergic synapse in specific brain regions has been shown to be a site for convergence of stress and addictive substances. The bed nucleus of the stria terminalis (BNST), a nucleus that relays between higher order processing centers and classical reward and stress pathways, receives dense noradrenergic inputs that are known to influence behavioral paradigms of both anxiety and stress-induced relapse to drug seeking. a 1 -Adrenergic receptors (a 1 -ARs) within this region have been implicated in modula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
69
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(73 citation statements)
references
References 55 publications
4
69
0
Order By: Relevance
“…Previous work has shown that bath application of the a1 AR agonist methoxamine (100 mM) for 20 min induces a1-LTD in the BNST that is modulated by chronic restraint stress (McElligott and Winder, 2008;McElligott et al, 2010). In this study, the same methoxamine application disrupted subsequent mGluR8-induced depression of excitatory transmission in the slice, as did both acute and chronic restraint stress.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Previous work has shown that bath application of the a1 AR agonist methoxamine (100 mM) for 20 min induces a1-LTD in the BNST that is modulated by chronic restraint stress (McElligott and Winder, 2008;McElligott et al, 2010). In this study, the same methoxamine application disrupted subsequent mGluR8-induced depression of excitatory transmission in the slice, as did both acute and chronic restraint stress.…”
Section: Discussionmentioning
confidence: 52%
“…The location of the a1 ARs disrupting mGluR8 function in the BNST is, as yet, unknown. Our lab has shown previously that postsynaptic G-protein signaling is necessary for expression of a1-LTD, suggesting a postsynaptic locus for a1 ARs (McElligott and Winder, 2008). One possibility is that postsynaptic a1 ARs are disrupting presynaptic mGluR8 via a retrograde messenger.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we described that mGluR5 activation induces LTD of excitatory transmission in the BNST (13). Additionally, norepinephrine (NE) can induce a time-dependent LTD via the α 1 -AR (19). A particularly interesting feature of α 1 -AR LTD is that it is heterosynaptic in nature in that it does not occur by augmenting NMDA receptor or mGluR5 signaling, although it can be elicited in the same neurons in BNST as mGluR5-LTD (19).…”
mentioning
confidence: 99%
“…Additionally, norepinephrine (NE) can induce a time-dependent LTD via the α 1 -AR (19). A particularly interesting feature of α 1 -AR LTD is that it is heterosynaptic in nature in that it does not occur by augmenting NMDA receptor or mGluR5 signaling, although it can be elicited in the same neurons in BNST as mGluR5-LTD (19). Based on this interaction and the studies in hippocampus (17) and visual cortex (18), we hypothesized that α 1 -AR LTD and mGluR5 LTD share common mechanisms and are recruited by similar environmental stimuli.…”
mentioning
confidence: 99%